Criminalisation of Service Users and Traditional Commercial Sex Workers in Indonesia - Nining; Ravena, Dey; Heniarti, Dini Dewi (Legalis : Journal of Law Review, 2024)
Law enforcement against service users and traditional commercial sex workers in Indonesia in handling the increasingly rampant practice of prostitution. Despite government efforts to reduce involvement in prostitution, the lack of specific regulations in Indonesian law has allowed service users of prostitution to avoid appropriate legal consequences. The purpose of this research is to understand the urgency to criminalize traditional commercial sex workers and service users. The majority of the problem lies in economic factors influenced by someone's income or needs, especially the difficulty for women to meet their needs, especially women who lack skills, thus their competitiveness in the job market is very low, and also related to the legal framework which still lacks regulation. This research uses a normative juridical method by employing legislative approach, conceptual approach, and comparative approach. Researchers examined secondary legal materials, including local regulations such as the DKI Jakarta Regional Regulation, the Indramayu District Regulation, the Tangerang City Regulation, the Denpasar City Regulation, the Badung Regency in Bali, Batam City, and Bandung Regency, as well as the Dutch regulation on brothels, known as the "Wet Regulering Prostitutie en Bestrijding Misstanden Seksbranche" (Regulation on Prostitution and Combating Abuses in the Sex Industry). The research findings indicate the need to promptly incorporate these regulations into the NATIONAL CRIMINAL CODE to prosecute users of traditional sex services and also the workers themselves, or at least to follow the policy of the Dutch government by legalizing brothels, where brothel owners are required to prove consistent tax payments and not being involved in any crimes, aiming to prevent HIV/AIDS and human trafficking.